2012
DOI: 10.1262/jrd.2011-019
|View full text |Cite
|
Sign up to set email alerts
|

Select Nutrients in the Uterine Lumen of Sheep and Pigs Affect Conceptus Development

Abstract: Abstract. Interferon tau (IFNT) is the pregnancy recognition signal from ruminant conceptuses. IFNT also acts with P4 to induce expression of genes for transport of nutrients, such as glucose (Gluc) and arginine (Arg) into the uterine lumen to activate mechanistic mammalian target of rapamycin (MTOR) cell signaling that stimulates proliferation, migration, gene transcription and mRNA translation by conceptus trophectoderm (Tr). In ewes, Arg and Gluc increase significantly in the uterine lumen between Days 10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 65 publications
(103 reference statements)
1
39
2
Order By: Relevance
“…Arg, Lys and His (all basic amino acids that share the same transport systems) are essential amino acids that cannot be synthesised by blastocysts, but are required during in vitro culture for murine blastocyst development and expansion, suggesting an important role during conceptus development and the establishment of pregnancy (for a review, see Bazer et al 2012). Subsequent studies revealed that Arg or Leu are central to murine blastocyst expansion and further development, initiating signalling pathways (including mammalian target of rapamycin), increasing mRNA expression and production of nitric oxide and polyamines essential for conceptus development and successful pregnancy (Bazer et al 2012). Other studies have demonstrated the importance of Arg during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arg, Lys and His (all basic amino acids that share the same transport systems) are essential amino acids that cannot be synthesised by blastocysts, but are required during in vitro culture for murine blastocyst development and expansion, suggesting an important role during conceptus development and the establishment of pregnancy (for a review, see Bazer et al 2012). Subsequent studies revealed that Arg or Leu are central to murine blastocyst expansion and further development, initiating signalling pathways (including mammalian target of rapamycin), increasing mRNA expression and production of nitric oxide and polyamines essential for conceptus development and successful pregnancy (Bazer et al 2012). Other studies have demonstrated the importance of Arg during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Orn is an intermediary in the synthesis of polyamines, derived from the conversion of Arg to Orn by arginase followed by conversion of Orn to polyamines by ornithine decarboxlyase (ODC1), which is essential for embryogenesis and placental development (Fozard et al 1980;Bazer et al 2012). Cys, a member of the functional amino acids (defined as regulators of key metabolic pathways benefiting survival, growth, development, reproduction and health; Wu et al 2009), has been shown to improve the development of porcine blastocysts in vitro (Choe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Histotroph composition has been widely investigated in the ewe (review Ref. 5), but in this species breeding occurs after weaning and is not concomitant with postpartum lipolysis and NEB induced by lactation as seen in postpartum cows. Lipid utilization for energy metabolism was recently demonstrated in early in vitro cultured bovine embryos (77), but there are no data to our knowledge about peri-implantation embryos.…”
Section: Metabolic Pathways Expressed In Conceptusesmentioning
confidence: 99%
“…Uterine luminal fluid samples of sheep, cattle, and pigs have been previously investigated to define adaptation in the uterine microenvironment in response to the presence of the conceptus (Bazer et al 2012). In the present study, gestational UF, collected at the time of embryo attachment, was investigated for its protein complement.…”
Section: Discussionmentioning
confidence: 99%